2015
DOI: 10.1007/s10854-015-3090-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CdCl2 treatment on deep levels in CdTe and their implications on thin film solar cells: a comprehensive photoluminescence study

Abstract: This work is aimed at studying defect level distributions in the bandgap of CdTe thin films, used for solar cell development. In particular, the effects of CdCl 2 treatment on the defect levels are the main objectives of this research. Four different CdTe thin films were electroplated using three different Cd-precursors (CdSO 4 , Cd(NO 3 ) 2 and CdCl 2 ), and bulk CdTe wafers purchased from industry (Eagle Pitcher and University Wafers in US) were studied using low temperature photoluminescence. The finger pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…The detailed results of this study are reported in a recent publication [55]. One example is shown in Fig.…”
Section: Removal Of Defects From the Materialsmentioning
confidence: 88%
See 3 more Smart Citations
“…The detailed results of this study are reported in a recent publication [55]. One example is shown in Fig.…”
Section: Removal Of Defects From the Materialsmentioning
confidence: 88%
“…This should be completely removed in order to produce high performance devices. These defects are also related to the Te-richness [55,56], and therefore to reduce these defects, material should be grown with Cd-richness, without Te-precipitation.…”
Section: Removal Of Defects From the Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Substitution of Cl into Te sites makes the material n-type by acting as a shallow donor [13]. However, there are experimental evidence of the formation of a defect level at 1.39 eV below the conduction band during CdCl 2 treatment [27]. This shows that during the CdCl 2 treatment, acceptor-like defect is also formed closer to the top of the valence band and this leads to the formation of p-type doping of CdTe.…”
Section: Photoelectrochemical (Pec) Cell Studymentioning
confidence: 99%